Application Of Edible Coating Aloe Vera On Langsat Punggur Pontianak To Extend Shelf Life - haloho, jhon; Liwu, Suzanne Laura; Barlina, Rindengan; Wungkana, Jerry (Politeknik Negeri Lampung., 2024)
Langsat Punggur Pontianak (Lansium parasiticum) has a high economic value in West Kalimantan, because it involves the thousands of workers who win it. Langsat Punggur Pontianak has unique nutritional and organoleptic characteristics. The purpose of this study was to evaluate the effectiveness of using edible coatings from aloe vera in extending the shelf life of Langsat Punggu Pontianak. The parameters for the tests carried out included weight loss, moisture content, TSS, texture, color, taste, aroma. The results showed that the use of edible coatings combined with cold temperatures could extend the shelf life to 15 days, and if Langsat Punggur Pontianak was stored at room temperature the shelf life would reach 10 days.